Beyond the hashtag – An exploration of tweeting and replies at the European Society of Surgical Oncology 39th clinical conference (ESSO39). Issue 7 (July 2020) - Mackenzie, Graham; Søreide, Kjetil; Polom, Karol; Lorenzon, Laura; Mohan, Helen; Guiral, Delia Cortés; Mayol, Julio
Abstract: Introduction: Previous studies of conference tweeting have focused on tweets that used the conference hashtag. The aim of this study was to document responses beyond a specific conference hashtag. Methods: Observational study exploring replies to tweets for the 39th meeting of ESSO (ESSO39), Rotterdam, 9–11 October 2019. An extract of #ESSO39 tweets was obtained using NodeXL. Replies to these tweets were identified by viewing the tweets via Twitter.com. Results: There were 210 tweets posted using the #ESSO39 hashtag by 64 tweeters. However, extending the analysis to include responses that did not use the hashtag, tweets using the hashtag only represent 54% of all tweets posted or quoted at the conference, and only 49% of the tweeters posting content or quoted in tweets. Based on this study of ESSO39 therefore roughly half of tweets and contributors to conference tweeting were not captured by focusing simply on the conference hashtag (#ESSO39). Mentioning another tweeter(s) in a tweet or response was associated with more retweets, as was including the hashtag in replies. Conclusions: Twitter activity at medical conferences extends beyond the conference hashtag. Almost half of the tweeting was beyond the hashtag. To increase visibility of tweets, conference delegates should include the conference hashtag and mention other tweeters in their tweets and responses. Searching for tweets is an active process requiring users to click into replies. Twitter and third-party social media tools should improve identification and display of responses, showing the branching structure of replies and quoting tweets in real time.